Determination of the effects of different high‐temperature treatments on texture and aroma characteristics in Alaska pollock surimi - Hua Zhang (Food Science & Nutrition, 2018)
Abstract This study tested the gel properties, quality of Alaska pollock surimi subjected to different temperature treatments. Results showed that when the heating temperature is 110°C, the water‐holding capacity (WHC) and texture of the surimi and gel strength increased, but as the heating temperature increased, the gel strength decreased significantly (p < 0.05), and ultimately destroyed. The heating temperature had no significant effect on the whiteness of the surimi gel, although it did have a significant effect on volatile components (p < 0.05). Fourier transform infrared (FT‐IR) spectroscopy suggested that with increasing temperature, protein secondary structure of the random coil received maximum damage, leading to protein aggregation and ultimately greatly reduced gel strength. At 100, 105, 110, 115, and 121°C, the surimi gel was determined 37, 46, 49, 52, and 56 volatile components, from of aldehydes, ketones, alcohols, hydrocarbons, and aromatic compounds. These results indicate that heat treatments have an important influence on the gel properties and volatile components of Alaskan pollock surimi gel, and the treatment parameters can be valuable for the production of ready‐to‐use minced fish products.